AN EXPERIMENTAL STUDY OF SIX DIFFERENT TYPES OF THE NATURAL FIBRES AS AN OIL SPILL ABSORPTION - Ismila Che Ishak; Mohd Fakhruddin Adli Mat Zaid; Muhammad Kasffi Ramli (Marine Frontier, 2020)
Marine pollution arises due to the harmful substances that arrive at the ecosystems because of human errors, technical errors, and natural errors. Once it happened, it triggered impacts on the environment, natural cycle, fishery industry, human life, marine life, economic and social. This study, directed by an on-site experimental to analyze the most oil absorption from six different types of natural fiber such as Fine Wood Dust, Coarse Sawdust, Coir, Kapok, Cattail, And Baggage. The experiment was steered in a fishing village at Kampung Nelayan Batu 1 located in Lumut, Perak. The objectives of this study are to rank the best oil absorption from six different types of natural fiber and to identify the absorption time and the quantity of absorbed oil from the six different types of natural fiber in absorbing the spilled oil created by the fishing boats. The result displays that Cattail is the most natural fiber in absorbing spilled oil from the water surface, followed by Kapok, Fine Wood Dust, Coir, Bagasse, and Coarse sawdust, respectively. The on-site experiment showed that a 100-gram cattail is desirable to absorb 50 milliliters of spilled oil within less than 6 hours. The experiment was manually performed and observed.